Reproductive and aggressive behaviours of queen–worker intercastes in the ant Mystrium rogeri and caste evolution. (October 2016) - Londe, Sylvain; Molet, Mathieu; Fisher, Brian L.; Monnin, Thibaud
Abstract : Evolutionary novelty can arise through the recombination of ancestral characters. In ants, colonies occasionally produce anomalous individuals that are mosaics of queen and worker characters. These intermediate individuals may be the first step in the evolution of new castes such as wingless queens and soldiers. While the morphological features of intercastes support this hypothesis, their rarity has meant their behaviour is unknown. In this study we carried out a behavioural study of 32 intercastes of Mystrium rogeri to assess whether they are a burden for their colonies, and whether their unusual morphologies are associated with consistent behavioural profiles and new functions. In addition, we measured dominance interactions within colonies, reproductive behaviours during dyadic encounters with males and aggressive interactions during dyadic encounters with heterospecific workers. We found that intercastes were active in colonies and that their behavioural profiles did not differ from those of virgin queens and workers. However, some intercastes were dominant, had developed ovaries and attracted males. One intercaste successfully mated and laid diploid eggs, demonstrating her reproductive potential. Moreover, we found that intercastes were as capable of fighting as workers because of their large size and could thus be useful for colony defence. Our results show that the production of intercastes in M. rogeri inflicts few costs but can yield benefits. Accordingly, certain ecological circumstances could select for increased frequency of intercaste production, ultimately resulting in the evolution of new reproductive and defensive castes. Highlights: Queen-worker intercastes are viable and express no aberrant behaviours. Some intercastes can reproduce sexually and may function as queens. Intercastes win fights against heterospecific ants and may benefit nest defence. With little cost and potential benefits, intercaste production may be favoured. Intercastes may be the first step in the evolution of novel castes in ants.